50th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2012
DOI: 10.2514/6.2012-979
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Chemical Kinetics on the Structure of Hydrogen-Air Detonations

Abstract: Two-dimensional simulations of a detonation propagating through a 4 cm wide channel filled with a stoichiometric hydrogen-air mixture using two different models for the chemical kinetics are presented: a single-step model calibrated to compute deflagrationto-detonation transitions in hydrogen-air mixtures and a 9-species, 27-reaction mechanism specially constructed for high-pressure combustion. The detonations in both cases are qualitatively similar. Shock triple points that form along the leading edge of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…Furthermore, 2-D CFD coupled to chemical kinetics resulted in a cell detonation width of 1 mm. In spite of being higher than the experimental values, these findings are usual for H2-air detonation (Gamezo et al, 1999) and other 2-D simulations with chemical kinetics had the same results (Taylor et al, 2012(Taylor et al, , 2013. Simulated reaction and induction zones with thickness around 2 mm and 0.5 mm, respectively, were found.…”
Section: Fig 3 Simulated H2-air Detonation Velocity Profiles In Thesupporting
confidence: 56%
See 2 more Smart Citations
“…Furthermore, 2-D CFD coupled to chemical kinetics resulted in a cell detonation width of 1 mm. In spite of being higher than the experimental values, these findings are usual for H2-air detonation (Gamezo et al, 1999) and other 2-D simulations with chemical kinetics had the same results (Taylor et al, 2012(Taylor et al, , 2013. Simulated reaction and induction zones with thickness around 2 mm and 0.5 mm, respectively, were found.…”
Section: Fig 3 Simulated H2-air Detonation Velocity Profiles In Thesupporting
confidence: 56%
“…The Green-Gauss node-based the second-order implicit method for transient formulation were applied. The setting of time-space discretization follows the works on H2-air detonation simulations (Srihari et al, 2015;Taylor et al, 2012Taylor et al, , 2013Sugiyama and Matsuo, 2012). Figure 1 shows the computational domain for the two-dimensional H2-air detonation simulation in an ideal PDE, where two regions are considered.…”
Section: Equation Discretizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In refs. [60,61] the structures obtained using detailed kinetic was not in good agreement with experimental results and it was commented that the problem in using detailed kinetic for extreme pressure and temperature caused this discrepancy. They reported that chemical kinetic mechanisms for combustion systems, in general, are not calibrated for simultaneous extremes of high pressure and temperature, such as those that occur in detonations.…”
Section: Governing Equationsmentioning
confidence: 75%
“…Much of detonation modelling has neglected diffusive processes, as their effects are thought to be small in comparison with advection and reaction (Shepherd 2009), cf. Fickett & Davis (1979), Oran et al (1998), Hu et al (2004Hu et al ( , 2005, Tsuboi, Eto & Hayashi (2007), Deiterding (2009) and Taylor et al (2012). However, Singh, Powers & Paolucci (1999) and Powers (2006), in a two-dimensional study of detonation patterns using a one-step kinetics model, † Email address for correspondence: cromick@nd.edu demonstrated that for the reactive Euler equations detonation patterns were griddependent.…”
mentioning
confidence: 97%